Measuring exchange market pressure and central bank intervention - Mikko Spolander (Bank of Finland, 1999)
This study contributes to the measurement of exchange market pressure and central bank intervention policy in a system of floating currency and partly sterilized foreign exchange interventions.A model-consistent approach is used.The measures of exchange market pressure and degree of intervention in the foreign exchange market are derived in the context of an empirically oriented small open economy monetary model with rational expectations.Monetary and foreign exchange policies are explicitly defined and foreign exchange interventions are allowed to be partly sterilized.Finally, the model is applied to Finnish data in order to analyse the pressure on the markka, which was floating during the period 1992-1996, and the Bank of Finland's reaction to that pressure.In contrast to most other empirical studies using various proxy variables, actual intervention data is used. According to the estimation results, the inclusion of the monetary policy reaction function and especially the sterilization of foreign exchange intervention makes the values of the measures of exchange market pressure and intervention policy more realistic and hence easier to interpret.This means that the fact that foreign exchange interventions are at least partly sterilized in the main industrial countries should be taken into account when exchange market pressure and central bank intervention policy are measured. This has not been done in other studies using a model-consistent approach.When the Bank of Finland's reaction to exchange market pressure is analysed, the results seem to suggest that the Bank let the markka float quite freely, reduced its intervention activity gradually as exchange market pressure diminished, and considered markka appreciation more desirable than depreciation during the markka float.
URN:NBN:fi:bof-201408071702
Keywords: 330; exchange market pressure; foreign exchange intervention; intervention policy; Finland